2004
DOI: 10.1016/j.molcel.2004.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Maturation of the U3 snoRNP in the Nucleoplasm in a Large Dynamic Multiprotein Complex

Abstract: The assembly and maturation of box C/D snoRNPs, factors essential for ribosome biogenesis, occur in the nucleoplasm. To investigate this process, we have analyzed non-snoRNP factors associated with the nucleoplasmic human U3 snoRNA. We show that both the precursor and mature length nucleoplasmic U3 snoRNAs are present in larger multiprotein complexes that contain the core box C/D proteins as well as many non-snoRNP factors linked to snoRNP assembly (TIP48, TIP49, Nopp140), RNA processing (TGS1, La, LSm4, hRrp4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
216
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(241 citation statements)
references
References 48 publications
20
216
0
1
Order By: Relevance
“…We have previously shown an overexpression of Reptin in hepatocellular carcinoma (8) and that Reptin silencing reduced tumor cell growth and viability in vitro (8,9), a finding confirmed by others in a number of cell lines of different origins (10)(11)(12). Remarkably, Reptin silencing in vivo led to regression of hepatocellular carcinoma tumor xenografts, in association with the induction of tumor cell senescence (9).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…We have previously shown an overexpression of Reptin in hepatocellular carcinoma (8) and that Reptin silencing reduced tumor cell growth and viability in vitro (8,9), a finding confirmed by others in a number of cell lines of different origins (10)(11)(12). Remarkably, Reptin silencing in vivo led to regression of hepatocellular carcinoma tumor xenografts, in association with the induction of tumor cell senescence (9).…”
Section: Introductionsupporting
confidence: 65%
“…Our data also lead us to conclude accordingly that antagonists of Reptin ATPase activity may be of benefit for the therapy of hepatocellular carcinoma. Besides hepatocellular carcinoma, an overexpression of Reptin has been shown in several types of tumors (2,11,12,27), and Reptin silencing also affects growth and viability of a variety of tumor cells (10)(11)(12). We thus propose that targeting Reptin ATPase activity may have broad applications in oncology.…”
Section: Discussionmentioning
confidence: 90%
“…To reduce expression levels of the Pontin protein HeLa cells were transiently transfected with two siRNA duplexes (21-mers with 3′-dTdT overhangs) as described in Watkins et al (2004). Following the protocol of Elbashir et al (2002), siRNA oligonucleotides were annealed to produce siRNA duplexes.…”
Section: Sirnamentioning
confidence: 99%
“…Small-interfering-RNA-mediated knockdown of La modestly decreased HeLa cell survival but was associated with more significant growth defects in the protozoan Trypanosoma brucei (10,32). A genetic analysis suggested that La is required during a late (larval) stage of development in Drosophila melanogaster (3).…”
mentioning
confidence: 99%